Pengaruh Range of Motion Terhadap Peningkatan Kemampuan Activity Daily Living pada Pasien Pasca Operasi Fraktur Ekstremitas Bawah: Narrative Review - Henny Yulianita; Firman Sugiharto; Nita Fitria; Dyah Setyorini; Andis Permana; Bunga Aviera; Dini Mulya; Fitri Yani; Meuthia Saulikha; Oktaviani Fauziah; Sarah Retno; Gihon Jessi (Universitas Malahayati Lampung, 2023)
ABSTRACT Postoperative fracture patients are prone to immobilization problems due to the appearance of pain so they feel afraid to move their limbs. Activity exercises that can be done for patients with postoperative lower extremity fractures are Range of Motion (ROM). The purpose of this review is to identify the effect of ROM intervention to increase Activity Daily Living (ADL) in lower extremity post-op patients. This research uses narrative review method. Literature search from the EBSCOhost, Garuda, and Google Scholar databases with the keywords ROM OR Range of Motion OR Range Of Movement” AND “Post-operative fracture OR Post-op Fractures” AND “Lower limb OR leg OR knee OR foot OR tibia OR femur” AND “Activity daily living OR Activity daily care OR ADL''. Articles were selected using the PRISMA 2020 guidelines. The results obtained were 5 articles that discussed ROM interventions to improve ADL. There are interventions in the form of active ROM and passive ROM. The conclusion that from the five articles analyzed, it was found that ROM intervention can be given to postoperative lower extremity fracture patients because it can improve ADL by reducing muscle and joint stiffness and preventing muscle atrophy in patients. Keyword: Activity Daily Living, Lower Limb, Range Of Motion. ABSTRAK Pasien post operasi fraktur rentan mengalami masalah imobilisasi akibat munculnya rasa nyeri sehingga mereka merasa takut untuk menggerakan anggota tubuhnya. Latihan aktivitas yang dapat dilakukan kepada pasien fraktur post operasi ekstremitas bawah adalah Range of Motion (ROM). Tujuan dari studi literatur ini adalah untuk mengidentifikasi pengaruh intervensi ROM untuk meningkatkan Activity Daily Living (ADL) pada pasien post-op ekstremitas bawah. Penelitian ini menggunakan metode narrative review. Pencarian literatur dari database EBSCOhost, Garuda, dan Google Scholar dengan kata kunci ROM OR Range of Motion OR Range Of Movement” AND “Post-operative fracture OR Post-op Fractures” AND “Lower limb OR leg OR knee OR foot OR tibia OR femur” AND “Activity daily living OR Activity daily care OR ADL’’. Artikel diseleksi menggunakan pedoman PRISMA 2020. Hasil didapatkan 5 artikel yang membahas intervensi ROM untuk meningkatkan ADL. Terdapat intervensi berupa ROM aktif dan ROM pasif. Dapat disimpulkan bahwa dari kelima artikel yang dianalisis didapatkan bahwa intervensi ROM dapat diberikan pada pasien fraktur post operasi ekstremitas bawah karena dapat meningkatkan ADL dengan mengurangi kekakuan otot dan sendi serta mencegah atropi otot pada pasien. Kata Kunci:Aktivitas Harian, Ekstremitas Bawah, Range of Motion.